Mavis Gallant’s Overhead in a Balloon: Politics and Religion, Language and Art - Woolford, Daniel (Studies in Canadian Literature, 1989)
Linguistics and post-structuralist criticism are observed in studying Mavis Gallant’s fiction. Through her characters, Gallant examines ideological issues such as sexism, imperialism, and nationalism. There is a constant collision of ideological perspectives so that the reader is alternately interpolated, drawn into events, and distanced thus engaging the reader into a critical debate. This collision, the tension between ideological perspectives, is what gives birth to art itself. Gallant also examines the uncomfortable relationships between art and money, and between politics and religion.